Hubungan Demensia Dengan Tingkat Kemandirian Activity Of Daily Living (ADL) Pada Lansia Di RT.04 RW.11 Jati Bening Pondok Gede Bekasi - Nurlan Nurlan; Kusdiah Eny (Afiat, 2021)
Dementia can affect the ability of daily activities because it is influenced by a collection of existing symptoms such as decreased cognitive function, changes in mood, and behavior. People with dementia in addition to experiencing gradual cognitive weakness, will also experience a decline in daily activities (Activity Of Daily Living / ADL). RW 11 Jatibening Pondok Gede Bekasi. Total population is 53 respondents. Samples were taken with a total sampling technique of 53 respondents. The analysis used univariate and bivariate using chi-square with =5%. The results of the study found that there was a relationship between dementia and the level of independence in Activity Of Daily Living (ADL) in the elderly at RT 04 RW 11 Jatibening Pondok Gede Bekasi. The conclusion is that the elderly who experience dementia in the category of mild intellectual impairment are people 30 (56.6%), the level of independence of the elderly in fulfilling the Activity Of Daily Living (ADL) in the category of mild dependence is 33 people (62.3%), and there is a relationship between There is a significant relationship between dementia and the level of independence of Activity Of Daily Living (ADL) in the Elderly In RT 04 RW 11 Jatibening Pondok Gede Bekasi. It is hoped that this research can provide information to the elderly with dementia so that they can continue to train their memory, as well as provide information to their families. so that it can provide motivation to family members in helping the elderly in meeting the needs of Activity Of Daily Living (ADL).